2021
DOI: 10.1111/gwat.13159
|View full text |Cite
|
Sign up to set email alerts
|

Coupling a Borehole Thermal Model andMT3DMSto Simulate Dynamic Ground Source Heat Pump Efficiency

Abstract: We present a novel integrated two-region model that couples simulation of local heat transfer processes in borehole heat exchangers (BHEs) with field-scale heat transport simulation using MT3DMS to fulfill the dynamic simulation of the borehole geothermal systems. This includes the prediction of subsurface thermal perturbation induced by BHEs, derivation of the U-pipe circulating fluid temperature profile within boreholes, and the evaluation of the ground source heat pump efficiency based on available time ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Heat transport can be simulated using the MT3DMS-USGS software (Bedekar et al, 2016), which is a numerical model for simulating advective and dispersive transport of conservative and non-conservative solutes in three-dimensional saturated subsurface flow systems. Hecht-Méndez et al (2010) demonstrated that MT3DMS is a suitable tool for simulating heat transport in the shallow subsurface due to the similarities between thermal and solute transport (Zheng, 2009;Zong et al, 2021).…”
Section: D Case Parameterizationmentioning
confidence: 99%
“…Heat transport can be simulated using the MT3DMS-USGS software (Bedekar et al, 2016), which is a numerical model for simulating advective and dispersive transport of conservative and non-conservative solutes in three-dimensional saturated subsurface flow systems. Hecht-Méndez et al (2010) demonstrated that MT3DMS is a suitable tool for simulating heat transport in the shallow subsurface due to the similarities between thermal and solute transport (Zheng, 2009;Zong et al, 2021).…”
Section: D Case Parameterizationmentioning
confidence: 99%
“…The MODFLOW groundwater model was applied for groundwater level simulation, and the MT3DMS model, in the form of an integrated model with MODFLOW, was used for aquifer-wide simulation of spatial distribution and concentration variation of total dissolved solids (TDS). A proper cell grid must be created following the conditions of the aquifer to simulate using the MODFLOW and MT3DMS models (Zong et al 2021). Various packages, including boundary conditions, quantitative and qualitative observation wells, hydrodynamic parameters (hydraulic conductivity, specific yield, longitudinal dispersivity, and effective porosity), recharge, and discharge, must be prepared to simulate groundwater's quantitative and qualitative behavior.…”
Section: The Numerical Modelsmentioning
confidence: 99%